2018
DOI: 10.1016/j.anireprosci.2018.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of plant- and egg yolk-based semen diluents on in vitro sperm kinematics and in vivo fertility of frozen-thawed bull semen

Abstract: Diluents using components of plant origin have been developed as an alternative to animal based extenders for the dilution of bull semen, however, it is unclear if use of these diluents results in in vivo fertility rates similar to those that occur with use of traditional egg yolk-based diluents. The aim of this study was to assess the effect of semen diluent on 60-day non-return rate (NRR) following artificial insemination (AI) with frozen-thawed bull semen. The effect of semen dilution in one of three differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 32 publications
6
25
0
Order By: Relevance
“…Moreover, Gillan et al (2008) suggested that the post-thawed sperm VSL is related directly to the bull fertility. Therefore, in the present study, a higher value of VCL and VSL in liposome-based extender might contribute towards better post-thawed semen quality and fertility such assumption was in accordance with Singh et al (2017) and Murphy et al (2018).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Moreover, Gillan et al (2008) suggested that the post-thawed sperm VSL is related directly to the bull fertility. Therefore, in the present study, a higher value of VCL and VSL in liposome-based extender might contribute towards better post-thawed semen quality and fertility such assumption was in accordance with Singh et al (2017) and Murphy et al (2018).…”
Section: Discussionsupporting
confidence: 71%
“…No differences between post-thawed sperm motility in semen which were extended with Optixcell® at 2 hours and 4 hours, Lima-verde et al (2017) revealed that sperm bull extended with Characteristics of Post-thawed Bali Bull Semen (A.S. Amal et al) 141 Optixcell® has improved mitochondrial membrane potential compared to soy-lecithin extender. Moreover, semen extended in Optixcell® had improved motility kinematic parameters than semen extended in Tris-cEY and Bioxcell® such a finding as previously suggested by Kumar et al (2015), Ansari et al (2016) and Murphy et al (2018). Liposomes behave similar to the cell membrane and adhere to the sperm membrane during cryopreservation, ensuring the exchange of cholesterol and phospholipids (Ansari et al, 2016).…”
Section: Discussionsupporting
confidence: 69%
“…Prior to the initiation of this study, it was anticipated that incorporation of PC liposome alone in the extender would improve the quality of cryopreserved ram semen, similarly to other species (He et al, 2001;Ropke et al, 2011;Pillet et al, 2012;Kumar et al, 2015). Murphy et al (2018) found that whereas extenders that contained plant-based liposome significantly reduced post-thaw sperm motility and kinematics. However, this semen produced 60-day nonreturn rates in cattle that were similar to semen frozen in egg yolk-based extender.…”
Section: Resultsmentioning
confidence: 99%
“…Liposomes are vesicular structures made of phospholipids in aqueous solution, arising from lipid bilayers organized concentrically, similar to biological membranes (Grad, 2010). Murphy et al (2018) and Luna-Orozco et al (2019) studied the effects of unspecified liposome and egg yolk based extenders in bull and ram semen, respectively. However, current information on ram semen cryopreservation using PC liposome in extender is limited.…”
Section: Introductionmentioning
confidence: 99%
“…There have been efforts to develop commercial extenders with defined contents and those that are free of animal products. Recent studies performed by Murphy et al (63) and Yodmingkwan et al (64) revealed that plant-based extenders can be efficiently used as alternatives to animal-based extenders in frozen semen to avoid spread of diseases. However, there are conflicting results related to the efficacy of lecithin-based extender for semen freezing.…”
Section: Extender Developmentmentioning
confidence: 99%